Diuretic and serum electrolyte regulation potential of aqueous methanolic extract of Solanum surattense fruit validates its folkloric use in dysuria. Issue 1 (December 2016) - Ahmed, Muhammad; Andleeb, Shumaila; Saqib, Fatima; Hussain, Musaddique; Khatun, Most.; Ch, Bashir; Rahman, Hafizur
Abstract Background Solanum surattense Burm. (Solanaceae) is traditionally used for management of various ailments. The study was conducted for provision of pharmacological justification for folkloric uses ofSolanum surattense in the treatment of dysuria. Methods Rats were randomly divided into 5 groups, each of (n = 6). Aqueous methanolic fruit extract ofS. surattense were also administered intraperitoneally to the rats at doses of 50, 70 and 100 mg/kg. Furosemide (10 mg/kg i.p) was used as standard drug whereas controls were given saline solution (40 mL/kg i.p). The electrolytes in urine were measured using a flame photometer whereas serum sodium, potassium, calcium, bicarbonate and blood urea nitrogen (BUN) were determined by using an automatic analyzer. Urine osmolality was assayed by the micro-osmometer. Results The extractS. surattense induced diuretic effects in a dose-dependent manner as compared with control. Upon administration of extract (70 and 100 mg/kg), we observed the prominent (p < 0.01) increase in the urine volume and osmolality in comparison to control group. However, plant extract (100 mg/kg) significantly increase the urinary electrolyte excretion especially calcium (p < 0.05) to that of the furosemide whereas level of magnesium remains constant. Moreover, our results showed a decrease in serum levels of sodium, potassium, calcium and blood urea nitrogen (BUN), but concentration dependent increase in bicarbonate was found in the test groups. There was no substantial change in the pH of urine samples of the extract-treated groups. Conclusion These results indicate thatS. surattense investigated exert its action by causing diuresis in the treatment of dysuria.